Integrated systems in a Brazilian university: Cooperative information as strategic resource - Márcia Josienne Monteiro Chacon; Daniel Carrasco Diaz; Daniel David Sanchez Toledano (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
The proposal discusses the obstacles arising from interconnected information systems that support the management in Brazilian federal public universities. Question the nature of information and sources that are used in the decision-making process by managers. It aims to analyze the information generated from the Management Information Systems in UFRN - Federal University of Rio Grande do Norte for decision making. This is a Case Study, which reflects the problems of the various institutions of higher education. Presented the system used in UFRN and its modules. It was concluded that the use of management systems are useful for Universities. It is observed that there are limitations that seek to overcome, such as asset control, module integration and system cost, with the possibility of implementing a Controller.
Keywords: 650; Information Systems; Business Intelligence; Universities Management